Single-crystal positive electrode material of solid-state battery, preparation method thereof, positive electrode and solid-state battery
Patent Information
- Application Number
- CN202611110537.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
当界面处的结合强度不足以抵抗该应力时,正极颗粒与硫化物电解质之间将逐步失去物理接触,形成“接触丧失”区域,导致电池容量快速衰减,循环寿命大幅缩短
本发明实施例提供的制备方法,其采用具有多级粒径的单晶正极材料基材和塑形剂一起烧结,塑形剂含有高n值元素。单晶正极材料基材含有大颗粒和小颗粒,大颗粒承重,小颗粒填缝,能极大地减少空隙;加入塑形剂进行混合烧结,塑形剂迁移至正极材料基材晶界,阻止正极材料原子跨越晶界,原子只能沿着颗粒表面进行短程扩散,在表面扩散作用下逐渐被“磨平”,使得烧结后制得的单晶正极材料表面无或少尖锐棱角,原本单晶正极材料基材表面的尖锐棱角全部或几乎全部被钝化,能使得在固态电池正极片制备过程中正极材料和电解质以及其他组分分布均匀性更好,有利于提高正极片的完整性;同时在固态电池工作过程中,无需高夹持压力,则能实现硫化物电解质与正极材料有效接触面积增大;棱角钝化后还能减少正极片应力集中的问题,能使正极材料颗粒裂纹减小,能极大地提高电池的容量和循环性能。
Smart Images

Figure CN122980031A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more specifically, to single-crystal cathode materials for solid-state batteries, their preparation methods, cathodes, and solid-state batteries. Background Technology
[0002] Sulfide solid electrolytes have high room temperature ionic conductivity (up to 10). 3 ~10 2 With its high efficiency (S / cm) and good machinability, sulfide electrolyte is considered one of the key materials for realizing high-energy-density all-solid-state batteries. However, when matching sulfide electrolyte with cathode material, several key issues restrict battery performance.
[0003] In all-solid-state batteries, a typical solid-solid interface is formed between the sulfide electrolyte and the positive electrode active material. Unlike traditional liquid electrolytes that can completely wet the electrode materials, gaps and pores exist at the solid-solid contact interface between the sulfide electrolyte and the positive electrode material. These physical defects severely restrict the transport path of lithium ions at the positive electrode / electrolyte interface, leading to uneven local ion flux, significantly increasing interfacial impedance, and consequently reducing the battery's rate performance and effective capacity utilization.
[0004] During actual charge-discharge cycles, the cathode material (especially high-nickel layered oxides) undergoes periodic contraction and expansion of its cell parameters, resulting in volume changes. This volume effect accumulates continuous mechanical stress at the solid-solid interface. When the bonding strength at the interface is insufficient to resist this stress, the cathode particles and the sulfide electrolyte will gradually lose physical contact, forming a "contact loss" region, leading to rapid capacity decay and a significant reduction in cycle life.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a single-crystal cathode material for solid-state batteries, a method for preparing the same, a cathode, and a solid-state battery, aiming to improve at least one of the problems mentioned in the background art.
[0007] This invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a single-crystal cathode material for a solid-state battery, comprising: providing a mixture, wherein the mixture is obtained by uniformly mixing a single-crystal cathode material substrate with a plasticizer, and the single-crystal cathode material substrate includes particles of a first particle size, particles of a second particle size, and particles of a third particle size; The first particle size is x, where 0.2μm ≤ x < 1μm, and the proportion of first-size particles is 10~20wt%. The second particle size is y, where 1μm ≤ y < 2μm, and the proportion of second particle size particles is 50~60 wt%. The third particle size is z, where 2μm ≤ z < 4μm, and the proportion of third particle size particles is 20~40 wt%. The mixture is sintered in an oxygen-containing atmosphere to obtain a single-crystal cathode material for solid-state batteries. The plasticizer is selected from at least one of the oxides and hydroxides of elements with high n values; The mass ratio of the single-crystal cathode material substrate to the plasticizer is 100:0.1~1; The sintering methods include: sintering at 400~500℃ for 3~5 hours, and then raising the temperature to 600~700℃ and sintering for 5~7 hours.
[0008] In an optional implementation, the high n-value element includes at least one of Mo, Zr, Ta, Nb, and W.
[0009] In an optional embodiment, the method of uniformly mixing the single-crystal cathode material substrate with the plasticizer includes: The monocrystalline cathode material substrate is placed in a fluidized bed, and gas is introduced to suspend the monocrystalline cathode material substrate. Then, a liquid containing a plasticizer is sprayed into the fluidized bed. The liquid containing the plasticizer collides with the monocrystalline cathode material substrate and is loaded onto the surface of the particles of the monocrystalline cathode material substrate. After instantaneous drying, a mixture is obtained.
[0010] In an optional embodiment, the liquid containing the plasticizer is a coating solution of the plasticizer and ethanol; Optionally, the concentration of the plasticizer in the coating solution is 0.1~0.5 g / mL; Optionally, the spraying rate of the liquid containing the plasticizer is 1.0~4.0 mL / min; Optionally, the instantaneous drying temperature is 100~140℃.
[0011] In an optional implementation, the oxygen-containing atmosphere is an oxygen atmosphere; Optionally, the flow rate of the oxygen atmosphere is 1~2 m³ / s. 3 / h.
[0012] In an optional embodiment, the method for preparing the single-crystal cathode material substrate includes: The single-crystal cathode materials with particle sizes of x, y and z are mixed uniformly to obtain a single-crystal cathode material substrate. The preparation methods for the single-crystal cathode materials to be matched for each particle size include: We offer a high-component mixture comprising a high-nickel precursor, a lithium source, and an alkaline earth metal compound. The high-nickel precursor has the chemical formula Ni. a Me1-a( OH)2, Me is one or more of Co, Al, Mn, Mg and Na, 0.7≤a≤1.0; The high-temperature sintered material is obtained by sintering the high-mixed material at 700~900℃ for 8~20h in an oxygen-containing atmosphere; The high-temperature sintering material is pulverized by airflow and then sieved to obtain the single-crystal cathode material to be prepared. Optionally, the oxygen-containing atmosphere is an oxygen atmosphere; Optionally, the sintering temperature is 750–850℃, and the sintering time is 10–20 h; Optionally, the oxygen flow rate during sintering is 1~2 m³ / s. 3 / h; Optionally, the molar ratio of lithium in the lithium source to Ni+Me in the high-nickel precursor is 1.02~1.10:1; Optionally, the lithium source is selected from at least one of lithium-containing oxides, hydroxides, and carbonates.
[0013] In an optional implementation, when it is necessary to prepare a single-crystal cathode material with a particle size of x, the mass ratio of alkaline earth metal to high-nickel precursor is 0.05~1.0:100. When it is necessary to prepare single-crystal cathode materials with a particle size of y, the mass ratio of alkaline earth metal to high-nickel precursor is 0.2~0.7:100. When it is necessary to prepare single-crystal cathode materials with a particle size of z, the mass ratio of alkaline earth metal to high-nickel precursor is 0.8~1.0:100. Optionally, the alkaline earth metal compound is selected from at least one of oxides, hydroxides, and carbonates of alkaline earth metals; the alkaline earth metal is selected from at least one of Ca, Sr, and Ba.
[0014] Secondly, the present invention provides a single-crystal cathode material for solid-state batteries, which is prepared by any of the preparation methods described in the foregoing embodiments.
[0015] Thirdly, the present invention provides a positive electrode whose active layer comprises a single-crystal positive electrode material as described in the foregoing embodiments.
[0016] Fourthly, the present invention provides a solid-state battery, including a positive electrode as described in the foregoing embodiments.
[0017] The present invention has the following beneficial effects: The preparation method provided in this invention uses a single-crystal cathode material substrate with multi-level particle sizes and a plasticizer sintered together, the plasticizer containing a high n-value element. The single-crystal cathode material substrate contains both large and small particles. The large particles bear the weight, while the small particles fill the gaps, greatly reducing voids. When a plasticizer is added and mixed for sintering, the plasticizer migrates to the grain boundaries of the cathode material substrate, preventing cathode material atoms from crossing these boundaries. Atoms can only diffuse along the particle surface in a short distance, gradually being "smoothed out" by surface diffusion. This results in a single-crystal cathode material surface with few or no sharp edges after sintering. The sharp edges of the original single-crystal cathode material substrate are completely or almost completely blunted, leading to better uniformity of the cathode material, electrolyte, and other components during solid-state battery cathode sheet preparation, thus improving the integrity of the cathode sheet. Simultaneously, during solid-state battery operation, high clamping pressure is not required, increasing the effective contact area between the sulfide electrolyte and the cathode material. Edge blunting also reduces stress concentration in the cathode sheet, decreasing particle cracks and significantly improving battery capacity and cycle performance. Attached Figure Description
[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 SEM image of the single-crystal cathode material of the solid-state battery prepared in Example 1; Figure 2 The image shows the size distribution diagram and the size distribution bar chart of the single crystal cathode material of the solid-state battery prepared in Example 1. Figure 3 SEM image of the single-crystal cathode material of the solid-state battery prepared in Comparative Example 10; Figure 4 SEM image of the single-crystal cathode material of the solid-state battery prepared in Comparative Example 11; Figure 5 SEM image of the single-crystal cathode material of the solid-state battery prepared in Comparative Example 7; Figure 6 SEM image of the single-crystal cathode material of the solid-state battery prepared in Comparative Example 9; Figure 7 SEM image of the single-crystal cathode material of the solid-state battery prepared in Comparative Example 16; Figure 8 The equivalent circuit diagram of the Nyquist plot of the impedance for testing the interface impedance of an all-solid-state lithium battery. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0021] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0022] This invention provides a method for preparing a single-crystal cathode material for a solid-state battery, comprising: providing a mixture, wherein the mixture is obtained by uniformly mixing a single-crystal cathode material substrate with a plasticizer, and the single-crystal cathode material substrate includes particles of a first particle size, particles of a second particle size, and particles of a third particle size; The particle size of the first particle size is x, where 0.2 μm ≤ x < 1 μm, and the proportion of particles of the first particle size is 10~20 wt%. The particle size of the second particle size is y, where 1μm ≤ y < 2μm, and the proportion of particles of the second particle size is 50~60 wt%. The third particle size has a particle size of z, where 2μm ≤ z < 4μm, and the proportion of the third particle size is 20~40wt%. The mixture is sintered in an oxygen-containing atmosphere to obtain the single-crystal cathode material of the solid-state battery; The plasticizer is selected from at least one of oxides and hydroxides of elements with high n values; The mass ratio of the single-crystal cathode material substrate to the plasticizer is 100:0.1~1; The sintering method includes: sintering at 400~500℃ for 3~5 hours, then raising the temperature to 600~700℃ and sintering for 5~7 hours.
[0023] The preparation method provided in this invention involves sintering a single-crystal cathode material substrate with multi-level particle sizes together with a plasticizer containing a high-n-value element. The single-crystal cathode material substrate contains both large and small particles; the large particles bear weight, while the small particles fill gaps, significantly reducing voids. During sintering at 400-500°C, the plasticizer removes a small amount of surface-adsorbed moisture and gradually adheres to the surface of the single-crystal cathode material substrate. At 600-700°C, the plasticizer migrates and anchors to the grain boundaries of the single-crystal cathode material substrate. Therefore, by adding the plasticizer and mixing for sintering, the plasticizer migrates to the grain boundaries of the cathode material substrate, preventing cathode material atoms from crossing the grain boundaries. Atoms can only diffuse along the particle surface in a short distance, gradually being "smoothed" by surface diffusion, thus improving sintering. The surface of the post-processed single-crystal cathode material has few or no sharp edges, and all or almost all of the sharp edges on the original single-crystal cathode material substrate surface are passivated. This allows for better uniformity of the distribution of cathode material, electrolyte, and other components during the preparation of solid-state battery cathode sheets, which is beneficial to improving the integrity of the cathode sheet. At the same time, during the operation of solid-state batteries, high clamping pressure is not required, which can increase the effective contact area between the sulfide electrolyte and the cathode material. After the edges are passivated, the problem of stress concentration in the cathode sheet can also be reduced, which can reduce the cracks in the cathode material particles and greatly improve the battery capacity and cycle performance.
[0024] It should be noted that in this invention, the high-n-value element is mixed and sintered with the single-crystal cathode material matrix after it has been obtained. This is because if a high-n-value element is introduced during the synthesis of the single-crystal cathode material matrix, it will inhibit particle growth, resulting in unsuitable particle sizes. Conversely, if a low-n-value element is added or directly sintered during the preparation of the single-crystal cathode material matrix, the sharp edges of the material particles will be noticeable.
[0025] The n-value refers to the coarsening index, D. t n -D0 n =k*(t t0); D t D0 and D0 are the average grain sizes at coarsening time t and initial time t0, respectively, after the addition of this element. k is a temperature-dependent material constant, and n reflects the control mechanism of grain growth. High n values: n > 2.
[0026] Optionally, high n-value elements include at least one of Mo, Zr, Ta, Nb, and W. These elements result in n > 2 in the three directions
[003] ,
[104] , and
[110] of the cathode material, creating additional resistance in these three directions. Atoms in the cathode material cannot cross grain boundaries to diffuse from small grains to large grains, thus suppressing grain boundary migration. Therefore, at high temperatures, high-energy atoms located at sharp edges easily migrate along the particle surface to adjacent low-energy planes (such as crystal planes or concave planes). As sharp atoms are lost, the edges naturally become "rounded".
[0027] Specifically, the preparation method is as follows: S1. Preparation of single-crystal cathode material substrate To prepare single-crystal cathode materials with three particle size scales of x, y and z, the three single-crystal cathode materials with particle size scales of x, y and z are mixed uniformly to obtain the single-crystal cathode material substrate.
[0028] Specifically, the preparation method of the single-crystal cathode material to be matched for each particle size includes: (1) Providing a high-mixture material, the high-mixture material comprising a high-nickel precursor, a lithium source and an alkaline earth metal compound, wherein the chemical formula of the high-nickel precursor is Ni a Me 1-a( OH)2, Me is one or more of Co, Al, Mn, Mg and Na, 0.7≤a≤1.0.
[0029] Optionally, when it is necessary to prepare the single-crystal cathode material to be prepared with a particle size of x, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.05~1.0:100; When it is necessary to prepare the single-crystal cathode material with a particle size of y, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.2~0.7:100. When it is necessary to prepare the single-crystal cathode material with a particle size of z, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.8~1.0:100.
[0030] Optionally, the lithium source is selected from at least one of lithium oxide, lithium carbonate, and lithium hydroxide.
[0031] Optionally, the molar ratio of lithium in the lithium source to Ni+Me in the high-nickel precursor is 1.02~1.10:1.
[0032] Optionally, the alkaline earth metal compound is selected from at least one of oxides, hydroxides, and carbonates of alkaline earth metals. The alkaline earth metal is selected from at least one of Ca, Sr, and Ba. At high temperatures, the alkaline earth metal compound can form a low-melting-point eutectic with the reactants, allowing the reactants to melt and flow at lower temperatures, thus promoting growth in slow-growing regions.
[0033] (2) The high-temperature sintering material with different particle sizes is obtained by sintering the high-temperature mixture in an oxygen-containing atmosphere. The sintering temperature is 700~900℃ and the time is 8~20h, preferably 750~850℃ for 10~20h.
[0034] Adding alkaline earth metal compounds as fluxes during sintering promotes grain nucleation and growth under milder thermal conditions, reducing Li volatilization and Li / Ni mixing at high temperatures; at the same time, no water washing step is required, simplifying the synthesis process, and without affecting capacity and cycle performance.
[0035] Optionally, the oxygen-containing atmosphere is an oxygen atmosphere. Optionally, the oxygen flow rate during sintering is 1~2 m³ / s. 3 / h.
[0036] (3) Crush different high-temperature sintering materials separately, and then sieve them (for example, sieve them with a sieve that meets the target particle size) to obtain single crystal cathode materials with particle sizes of x (first particle size), y (second particle size), and z (third particle size). Single-crystal cathode materials of different particle sizes are mixed uniformly to obtain a single-crystal cathode material substrate.
[0037] The pulverization method is air jet milling, and the mixing method is dry mixing. Air jet milling prevents weakly bonded agglomerated particles from separating, resulting in dispersed single-crystal cathode material. At the same time, air jet milling ensures that the crystal structure of the material is not damaged, ensuring excellent cycle performance after pulverization.
[0038] Specifically, the mixture is prepared by mixing single-crystal cathode materials with particle size x as 10~20wt%, single-crystal cathode materials with particle size y as 50~60wt%, and single-crystal cathode materials with particle size z as 20~40wt%.
[0039] The particle size distribution of the aforementioned particles ensures that the final cathode material also has a similar particle size distribution. When applied to the cathode active layer of a solid-state battery, it can improve the effective contact between the cathode material and the sulfide solid electrolyte, achieving a structure of "large particles bearing the weight and small particles filling the gaps." This can greatly improve the density of the electrode, reduce voids, and thus change the contact between the sulfide electrolyte and the cathode from "point contact" to "surface contact," effectively reducing interfacial impedance.
[0040] S2, Mix A single-crystal cathode material substrate comprising particles of a first size, a second size, and a third size is placed in a fluidized bed. Gas is introduced to suspend the single-crystal cathode material substrate. Then, a liquid containing a plasticizer is sprayed into the fluidized bed. The liquid containing the plasticizer collides with the single-crystal cathode material substrate and is loaded onto the particle surface of the single-crystal cathode material substrate. After instantaneous drying, a mixture is obtained.
[0041] Optionally, the liquid containing the plasticizer is a coating solution of the plasticizer and ethanol. Using ethanol as a carrier, it is volatile and can achieve a good instantaneous drying effect.
[0042] Optionally, the concentration of the plasticizer in the coating solution is 0.1~0.5 g / mL. The spraying rate of the liquid containing the plasticizer is 1.0~4.0 mL / min. At this concentration and spraying rate, a suitable amount of plasticizer loading can be ensured on the surface of the single-crystal cathode material substrate particles.
[0043] Optionally, the instantaneous drying temperature is 100~140℃. Instantaneous drying can be achieved at this temperature.
[0044] S3, sintering The mixture is sintered at 400-500℃ for 3-5 hours in an oxygen-containing atmosphere, and then the temperature is increased to 600-700℃ for 5-7 hours.
[0045] In this step, at 400~500℃, the plasticizer removes a small amount of moisture adsorbed on the surface and gradually adheres to the surface of the single-crystal cathode material substrate. At 600~700℃, the plasticizer migrates and pins to the grain boundaries of the single-crystal cathode material substrate.
[0046] Optionally, the oxygen-containing atmosphere is an oxygen atmosphere.
[0047] Optionally, the flow rate of the oxygen atmosphere is 1~2 m³ / s. 3 / h.
[0048] The single-crystal cathode material for solid-state batteries provided in this embodiment of the invention is prepared using the preparation method provided in this embodiment of the invention.
[0049] The positive electrode provided in this embodiment of the invention has an active layer comprising the single-crystal positive electrode material provided in this embodiment of the invention.
[0050] The solid-state battery provided in this embodiment of the invention includes a positive electrode provided in this embodiment of the invention.
[0051] Example 1 S1、 A high-nickel precursor, a lithium source, and an alkaline earth metal compound are uniformly mixed to obtain a high-mixture. The chemical formula of the high-nickel precursor is Ni. 0.9 Co 0.05 Mn 0.05 (OH)2, the lithium source is lithium hydroxide, the lithium:(Ni+Me) ratio is 1.07:1, and the alkaline earth metal compound is barium carbonate.
[0052] Barium carbonate, a high-nickel precursor, and a lithium source were mixed and sintered under an oxygen atmosphere (flow rate 1.5 m³ / s). 3 Sintering at 780℃ for 15 hours, followed by air jet pulverization and sieving, yielded single-crystal cathode material. Three types of single-crystal cathode materials with particle sizes x, y, and z were prepared using this method, where 0.2μm ≤ x < 1μm, 1μm ≤ y < 2μm, and 2μm ≤ z < 4μm.
[0053] When preparing single-crystal cathode material with particle size x, the mass ratio of barium carbonate to high-nickel precursor is 0.07:100; when preparing single-crystal cathode material with particle size y, the mass ratio of barium carbonate to high-nickel precursor is 0.5:100; and when preparing single-crystal cathode material with particle size z, the mass ratio of barium carbonate to high-nickel precursor is 0.9:100.
[0054] Single-crystal cathode materials with particle sizes of x, y and z were mixed at mass percentages of 15wt%, 55wt% and 30wt% to obtain a substrate containing single-crystal cathode materials with different particle sizes.
[0055] S2, A molybdenum oxide coating solution with a concentration of 0.3 g / mL was prepared using anhydrous ethanol as a solvent. Next, the uniformly mixed single-crystal cathode material matrix of different particle sizes from S1 was placed at the bottom of a fluidized bed, and a 0.15 m³ / mL gas flow was introduced. 3 The airflow of / h causes the matrix material to be in a suspended fluidized state in the fluidized bed. The mass ratio of molybdenum oxide in the molybdenum oxide coating solution to the single crystal cathode material substrate is 0.5:100. The molybdenum oxide coating solution is sprayed into the bed at a spraying rate of 2.5mL / min. After the molybdenum oxide coating solution collides and adsorbs with the matrix material particles, it is then instantaneously dried at 120℃ to obtain the treated material.
[0056] S3 The material was sintered in an oxygen atmosphere for 4 hours at 450°C in the first stage, followed by a second stage sintering at 650°C for 6 hours. The oxygen flow rate was 1.5 m³ / h. 3 / h.
[0057] The single-crystal cathode material for solid-state batteries was fabricated, and the SEM image is shown below. Figure 1 As shown in the figure, the particle surface has few or no sharp edges. The size distribution and histogram of the single-crystal cathode material prepared in this embodiment are shown below. Figure 2 As shown in the figure, the single-crystal cathode material is composed of a combination of large and small particle sizes, which enables large particles to bear the weight and small particles to fill the gaps, thus greatly reducing voids.
[0058] Example 2 This embodiment is basically the same as Embodiment 1, except that: The alkaline earth metal compound is calcium carbonate.
[0059] Example 3 This embodiment is basically the same as Embodiment 1, except that: The alkaline earth metal compound is strontium carbonate.
[0060] Example 4 This embodiment is basically the same as Embodiment 1, except that: In step S2, a zirconium oxide coating solution is used as the coating solution.
[0061] Example 5 This embodiment is basically the same as Embodiment 1, except that: In step S2, tantalum oxide coating solution is used as the coating solution.
[0062] Example 6 This embodiment is basically the same as Embodiment 1, except that: In step S2, niobium oxide coating solution is used as the coating solution.
[0063] Example 7 This embodiment is basically the same as Embodiment 1, except that: In step S2, tungsten oxide coating solution is used as the coating solution.
[0064] Example 8 In step S1, the particle sizes x, y, and z account for 20 wt%, 60 wt%, and 20 wt%, respectively. The sintering temperature was 700℃ and the sintering time was 20 hours.
[0065] In step S2, the concentration of the molybdenum oxide coating solution is 0.5 g / mL, and the mass ratio of molybdenum oxide to the single-crystal cathode material substrate is 0.1:100.
[0066] In step S3, the first sintering temperature is 400℃ and the time is 3h, and the second sintering temperature is 600℃ and the time is 7h.
[0067] Example 9 In step S1, the particle sizes x, y, and z account for 10 wt%, 50 wt%, and 40 wt%, respectively. The sintering temperature was 900℃ and the sintering time was 8 hours.
[0068] In step S2, the concentration of the molybdenum oxide coating solution is 0.1 g / mL, and the mass ratio of molybdenum oxide to the single-crystal cathode material substrate is 1:100.
[0069] In step S3, the first sintering temperature is 500℃ and the time is 5h, and the second sintering temperature is 700℃ and the time is 5h.
[0070] Comparative Example 1 This comparative example is basically the same as Example 1, except that: Single-crystal cathode material with a particle size of x is directly used as the substrate of single-crystal cathode material.
[0071] Comparative Example 2 This comparative example is basically the same as Example 1, except that: Single-crystal cathode material with a particle size of y is directly used as the substrate of single-crystal cathode material.
[0072] Comparative Example 3 This comparative example is basically the same as Example 1, except that: Single-crystal cathode material with a particle size of z is directly used as the substrate of single-crystal cathode material.
[0073] Comparative Example 4 This comparative example is basically the same as Example 1, except that: A single-crystal cathode material with particle size x and a single-crystal cathode material with particle size y are mixed as a single-crystal cathode material substrate, with the two having a mass ratio of 20wt% and 80wt%, respectively.
[0074] Comparative Example 5 This comparative example is basically the same as Example 1, except that: A single-crystal cathode material with a particle size of x and a single-crystal cathode material with a particle size of z are mixed as a single-crystal cathode material substrate, with the two having a mass ratio of 33wt% and 67wt%, respectively.
[0075] Comparative Example 6 This comparative example is basically the same as Example 1, except that: A single-crystal cathode material with a particle size of y and a single-crystal cathode material with a particle size of z are mixed as a single-crystal cathode material substrate, with the two having a mass ratio of 65wt% and 35wt%, respectively.
[0076] Comparative Example 7 This comparative example is basically the same as Example 1, except that steps S2 and S3 are omitted.
[0077] Comparative Example 8 This comparative example is basically the same as Example 1, except that: In step S2, the mass ratio of molybdenum oxide in the coating solution to the single-crystal cathode material substrate is 2.0:100.
[0078] Comparative Example 9 This comparative example is basically the same as Example 1, except that: In step S2, molybdenum oxide is replaced with an equal mass of aluminum oxide.
[0079] Comparative Example 10 This comparative example is basically the same as Example 1, except that: In step S1, no alkaline earth metal compounds were added during the preparation of the single-crystal cathode material.
[0080] Comparative Example 11 This comparative example is basically the same as Example 1, except that: In step S1, the alkaline earth metal compound is silicon carbonate.
[0081] Comparative Example 12 This comparative example is basically the same as Example 1, except that: In step S1, sintering is carried out at 650℃ for 20 hours.
[0082] Comparative Example 13 This comparative example is basically the same as Example 1, except that: In step S1, sintering is carried out at 950℃ for 8 hours.
[0083] Comparative Example 14 This comparative example is basically the same as Example 1, except that: In step S3, the second stage involves sintering at 750℃ for 5 hours.
[0084] Comparative Example 15 This comparative example is basically the same as Example 1, except that: In step S3, the second stage involves sintering at 350℃ for 10 hours.
[0085] Comparative Example 16 This comparative example is basically the same as Example 1, except that: Molybdenum oxide is added and sintered together in step S1; steps S2 and S3 are omitted.
[0086] Experimental Example Solid-state batteries were fabricated using the single-crystal cathode materials obtained in the various embodiments and comparative examples, and their electrochemical performance was measured.
[0087] Sulfide solid-state battery assembly: A composite cathode was prepared by mixing a monocrystalline cathode material, a sulfide electrolyte, and conductive carbon in a mass ratio of 70:27:3 and grinding the mixture for 30 minutes until homogeneous. An appropriate amount of the sulfide solid electrolyte was placed into the inner liner of a molded battery, pressurized to 300 MPa, and held for 1 minute to obtain the electrolyte layer. The composite cathode was then evenly spread on one side of the electrolyte layer, with a cathode loading of 20 mg / cm³. 2 The pressure was increased to 300 MPa and held for 1 minute to obtain the positive electrode active material layer. Indium and lithium metal sheets were placed on the other side of the electrolyte layer, and the pressure was increased to 120 MPa and held for 1 minute to obtain the negative electrode layer. The sealed mold battery liner was then placed in a fixture and clamped at a pressure of 80 MPa to obtain a sulfide solid-state battery. All the above operations were performed in an argon atmosphere glove box, where the water and oxygen levels were all less than 0.01 ppm.
[0088] Porosity testing: The densities of the single-crystal cathode material, sulfide electrolyte, and conductive carbon were measured using a true density analyzer and denoted as ρ. NCM ρ SE and ρ C The porosity ŋ is obtained using the following formula:
[0089] Where m is the mass of the composite positive electrode, h is the thickness of the composite positive electrode, and S is the area of the composite positive electrode.
[0090] Capacity test: The all-solid-state battery was left to stand for 10 minutes in a constant temperature environment of 25℃, then charged to 3.7V at 0.1C, and then discharged at a constant current rate of 0.1C to a voltage of 1.9V. The discharge capacity at this time was recorded.
[0091] Cyclic testing: The all-solid-state battery was placed at a constant temperature of 25℃ for 10 minutes, then charged at 0.1C to 3.7V, and then discharged at a constant current rate of 0.1C to 1.9V. This process was repeated once for activation. Next, it was charged at a constant current rate of 0.33C to 3.7V, and then discharged at a constant current rate of 0.33C to 1.9V, completing one charge-discharge cycle. This process was repeated. The capacity (D1) at the end of the first cycle and the capacity (D50) at the end of the 50th cycle were recorded. The cycle performance is the ratio of the discharge capacity after 50 cycles at 1C to the discharge capacity of the first cycle.
[0092] AC Impedance Interval (EIS) Testing: AC impedance testing was performed using an electrochemical workstation. The interfacial impedance of the all-solid-state lithium battery was tested, and the Nyquist plot of the impedance and the equivalent circuit diagram are shown below. Figure 8 As shown, Rs is related to the electrolyte resistance; Rct1 is related to the interface impedance between the Li-In alloy negative electrode and the sulfide solid electrolyte; Rct2 is related to the interface impedance between the positive electrode and the sulfide solid electrolyte; and Rw is related to the diffusion coefficient.
[0093] Test results: SEM images, size distribution diagrams, and size distribution histograms of the single-crystal cathode material prepared in Example 1 are shown in the attached figures. Figure 1 and Figure 2 It can be concluded that: using different particle sizes for mixing, with uniform distribution of different particle sizes, and the size distribution ranging from 0.2 to 4.0 micrometers in a staged manner, is beneficial for the structure of large particles bearing the weight and small particles filling the gaps in the composite positive electrode sheet; the surface of the single crystal positive electrode material obtained by sintering the uniformly mixed positive electrode material matrix of different sizes and the plasticizer has no or few sharp edges, and the sharp edges of the original single crystal positive electrode material substrate are all or almost all blunted.
[0094] SEM images of the single-crystal cathode materials for solid-state batteries prepared using Comparative Examples 10 and 11 are shown in [reference 1]. Figure 3 and Figure 4 It can be concluded that: without the use of alkaline earth metal compounds or other additives for high-temperature sintering, the particle size is relatively small and the size does not show a staged distribution.
[0095] SEM images of the single-crystal cathode materials for solid-state batteries prepared using Comparative Examples 7 and 9 are shown in [reference 1]. Figure 5 and Figure 6 We can conclude that: with Figure 1 contrast, Figure 5 The surface of the particles clearly has sharp edges and corners. Figure 6 Particle surface is relatively Figure 5 The sharp edges are noticeably blunted, but the grain morphology is still not as good as... Figure 1 Round and smooth.
[0096] SEM images of the single-crystal cathode material used in the solid-state battery prepared in Comparative Example 16 are shown below. Figure 7 We can conclude that: Figure 7 The particles are small and clustered, inferior to... Figure 1 The particles are distributed in stages of size and are dispersed.
[0097] The test results of each embodiment and comparative example are recorded in Table 1.
[0098] Table 1 Test results for each embodiment and comparative example
[0099] As can be seen from Table 1, the cathode materials prepared in the various embodiments of the present invention exhibit excellent electrochemical performance when applied in solid-state batteries, which is significantly better than that of conventional cathode materials (comparative examples).
[0100] Comparing Comparative Examples 1-6 with Examples 1 and 8-9, the porosity of the comparative examples is significantly greater than that of the examples. At the same time, the porosity changes with different ratios of the first, second, and third particle sizes, indicating that large particles bear the weight and small particles fill the gaps, which can greatly reduce the porosity of the composite cathode, increase the density of the electrode, increase the effective contact area between the sulfide electrolyte and the cathode, reduce the interfacial impedance, thereby increasing the capacity of the cathode material and improving the capacity retention rate. Compared with Example 1, Comparative Examples 10-11 did not involve alkaline earth metals in the synthesis process of the cathode material, or used other additives. The particle size was uniform, and the low porosity of the composite cathode sheet could not be achieved. The impedance was high, the capacity was low, and the cycle performance was poor. Compared with Examples 1 and 8-9, Comparative Examples 12-13 show that if the sintering temperature is too low, the particle size is too small, and it is impossible to obtain a suitable large particle size, resulting in more pores in the composite positive electrode sheet; if the sintering temperature is too high, the particle size is too large, and it is impossible to obtain a suitable small particle size, resulting in more pores in the composite positive electrode sheet. With more pores, ion transport is hindered, impedance increases, and capacity and cycle performance decrease. Comparing Comparative Examples 7-8 with Examples 1 and 8-9, Comparative Example 7 has more pronounced edges and corners, the contact between the cathode material and the electrolyte and conductive carbon is more loose, the porosity is greater, the impedance is increased, and the capacity and cycle performance are reduced. Compared with Example 1, Comparative Example 8 has too much molybdenum oxide, and the particle edges and corners are blunted. However, due to the excessive Mo content, there is more surface adhesion, which increases the impedance and is not conducive to the capacity of the cathode material. Compared with Comparative Example 9 and Examples 1 and 4-7, Comparative Example 9 uses alumina, and n≈2 in the three directions
[003] ,
[104] , and
[110] . There is less additional resistance in the three directions, and the atoms of the cathode material can easily cross the grain boundary. When added to the synthesis process of single-crystal cathode material substrate, it cannot play an obvious role in blunting the edges and corners, and cannot significantly improve the electrochemical performance of the cathode material. Compared with Examples 1 and 8-9, Comparative Examples 14-15 show that if the sintering temperature is too high, Mo will enter the surface layer of the cathode material, generating substances that are not conducive to lithium-ion transport, increasing the interfacial impedance, and hindering the capacity of the cathode material; if the sintering temperature is too low, its passivation effect on the material surface is not obvious, the porosity increases, and the capacity and cycle performance decrease. Compared with Example 1, Comparative Example 16 has agglomerated particles with small size, increased porosity of the cathode material, electrolyte, and conductive carbon, increased interfacial impedance, and poor capacity and cycle performance.
[0101] In summary, the method for preparing single-crystal cathode material for solid-state batteries provided by this invention, after mixing different particle sizes, allows large particles to bear weight while small particles fill gaps, greatly reducing voids. Adding a plasticizer for mixing and sintering allows the plasticizer to migrate to the grain boundaries of the cathode material substrate, preventing cathode material atoms from crossing these boundaries. Atoms can only diffuse along the particle surface in a short distance, gradually being "polished" by surface diffusion. Therefore, the surface of the single-crystal cathode material obtained after sintering has few or no sharp edges. All or almost all of the sharp edges on the original surface of the single-crystal cathode material substrate are blunted, resulting in better uniformity of the cathode material, electrolyte, and other components during the solid-state battery cathode sheet preparation process, which is beneficial for improving the integrity of the cathode sheet. High clamping pressure is not required, thus increasing the effective contact area between the sulfide electrolyte and the cathode material. Simultaneously, the blunting of the edges reduces stress concentration in the cathode sheet, decreases particle cracks in the cathode material, and improves the battery's capacity and cycle performance.
[0102] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a single-crystal cathode material for a solid-state battery, characterized in that, include: A mixture is provided, which is obtained by uniformly mixing a single-crystal cathode material substrate with a plasticizer, wherein the single-crystal cathode material substrate includes particles of a first particle size, particles of a second particle size, and particles of a third particle size; The particle size of the first particle size is x, where 0.2 μm ≤ x < 1 μm, and the proportion of particles of the first particle size is 10~20 wt%. The particle size of the second particle size is y, where 1μm ≤ y < 2μm, and the proportion of particles of the second particle size is 50~60 wt%. The third particle size has a particle size of z, where 2μm ≤ z < 4μm, and the proportion of the third particle size is 20~40wt%. The mixture is sintered in an oxygen-containing atmosphere to obtain the single-crystal cathode material of the solid-state battery; The plasticizer is selected from at least one of oxides and hydroxides of elements with high n values; The mass ratio of the single-crystal cathode material substrate to the plasticizer is 100:0.1~1; The sintering method includes: sintering at 400~500℃ for 3~5 hours, then raising the temperature to 600~700℃ and sintering for 5~7 hours.
2. The preparation method according to claim 1, characterized in that, The high n-value elements include at least one of Mo, Zr, Ta, Nb, and W.
3. The preparation method according to claim 1, characterized in that, The method of uniformly mixing the single-crystal cathode material substrate with the plasticizer includes: The single-crystal cathode material substrate is placed in a fluidized bed, and gas is introduced to suspend the single-crystal cathode material substrate. Then, a liquid containing the plasticizer is sprayed into the fluidized bed. The liquid containing the plasticizer collides with the single-crystal cathode material substrate and is loaded onto the surface of the particles of the single-crystal cathode material substrate. After instantaneous drying, the mixture is obtained.
4. The preparation method according to claim 3, characterized in that, The liquid containing the plasticizer is a coating solution of the plasticizer and ethanol; Optionally, the concentration of the plasticizer in the coating solution is 0.1~0.5 g / mL; Optionally, the spraying rate of the liquid containing the plasticizer is 1.0~4.0 mL / min; Optionally, the instantaneous drying temperature is 100~140℃.
5. The preparation method according to claim 1, characterized in that, The oxygen-containing atmosphere is an oxygen atmosphere; Optionally, the flow rate of the oxygen atmosphere is 1~2 m³ / s. 3 / h.
6. The preparation method according to claim 1, characterized in that, The method for preparing the single-crystal cathode material substrate includes: The single-crystal cathode material to be prepared is uniformly mixed with three particle size scales of x, y and z to obtain the single-crystal cathode material substrate; The preparation method of the single-crystal cathode material to be matched for each particle size includes: A high-mixture compound is provided, comprising a high-nickel precursor, a lithium source, and an alkaline earth metal compound, wherein the high-nickel precursor has the chemical formula Ni. a Me 1-a( OH)2, Me is one or more of Co, Al, Mn, Mg and Na, 0.7≤a≤1.0; The high-temperature sintered material is sintered at 700-900°C for 8-20 hours in an oxygen-containing atmosphere to obtain a high-temperature sintered material. The high-temperature sintering material is pulverized by airflow and then sieved to obtain the single-crystal cathode material to be prepared. Optionally, the oxygen-containing atmosphere is an oxygen atmosphere; Optionally, the sintering temperature is 750–850℃, and the sintering time is 10–20 h; Optionally, the oxygen flow rate during sintering is 1~2 m³ / s. 3 / h; Optionally, the molar ratio of lithium in the lithium source to Ni+Me in the high-nickel precursor is 1.02~1.10:1; Optionally, the lithium source is selected from at least one of lithium-containing oxides, hydroxides, and carbonates.
7. The preparation method according to claim 6, characterized in that, When it is necessary to prepare the single-crystal cathode material with a particle size of x, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.05~1.0:
100. When it is necessary to prepare the single-crystal cathode material with a particle size of y, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.2~0.7:100; When it is necessary to prepare the single-crystal cathode material with a particle size of z, the mass ratio of the alkaline earth metal to the high-nickel precursor is 0.8~1.0:
100. Optionally, the alkaline earth metal compound is selected from at least one of oxides, hydroxides, and carbonates of alkaline earth metals; the alkaline earth metal is selected from at least one of Ca, Sr, and Ba.
8. A single-crystal cathode material for a solid-state battery, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.
9. A positive electrode, characterized in that, Its active layer includes the single-crystal cathode material as described in claim 8.
10. A solid-state battery, characterized in that, Includes the positive electrode as described in claim 9.